Understanding the Experiences of Women with Gestational Diabetes in Singapore: A Qualitative Study - Lazarus MA; Lee VV; Ong DLS; Yew TW; Shorey S; Young D; Eriksson JG (International Journal of Women's Health, 2025)
Monica Ashwini Lazarus,1,2 V Vien Lee,1 Desmond Luan Seng Ong,3 Tong Wei Yew,4 Shefaly Shorey,5 Doris Young,1 Johan Gunnar Eriksson2,6 1Division of Family Medicine, Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 2Human Potential Translational Research Programme, Yong Loo Lin School of Medicine, Singapore; 3National University Polyclinics, National University Health System, Singapore; 4Division of Endocrinology, Department of Medicine, National University Hospital, Singapore; 5Alice Lee Centre for Nursing Studies, Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 6Department of Obstetrics & Gynaecology, Yong Loo Lin School of Medicine, National University of Singapore, SingaporeCorrespondence: Monica Ashwini Lazarus, Yong Loo Lin School of Medicine, Dean’s Office, Human Potential TRP, 10 Medical Drive, Block MD 11, #03-10, 117597, Singapore, Email mdcmal@nus.edu.sgPurpose: Gestational Diabetes Mellitus (GDM) is common in Southeast Asian countries. In Singapore, GDM affects approximately one in five pregnancies. Women diagnosed with GDM are at greater risk of developing type 2 Diabetes Mellitus. Little is known about how women with GDM manage the complex interactions between provider demands, personal responsibility, and family relationships. Accordingly, this study aimed to explore how women and their spouses experience GDM, from diagnosis to long-term management.Patients and Methods: Individual semi-structured interviews were conducted with 19 women who had GDM in the past five years (2019– 2023). Five spouses were interviewed for this study. The interviews were audio-recorded, transcribed, and analyzed using Braun and Clarke’s reflexive thematic analysis.Results: We report three themes: diagnosis, management, and long-term experience. During the GDM diagnosis, women described feeling blindsided and emotionally overwhelmed. In GDM management, women struggle to find information and healthcare support. Some women’s families were sources of support whereas other women must navigate family attitudes toward GDM that may be counterproductive. Postdelivery, women are unclear about follow-up procedures, feel neglected by the healthcare system in terms of their history of GDM, and struggle to make sustained changes to their individual and family health.Conclusion: Women with GDM face emotional and informational challenges that begin at diagnosis and persist after delivery. Better GDM education and follow-up care encouraging family-centered support will improve long-term outcomes.Keywords: gestational diabetes, health belief model, women, spouses, qualitative research